Lectin profile of rat cardiac cells on the stages of embryonic and postnatal development. - Yashchenko, A. M. (Морфологія / Morphologia / Morfologìâ, 2013)
The distribution of the lectin-receptors for WGA, LCA, RCAI, LAL, PSA, PFA, UeA, PNAin the embryonic hearts of the rat embryos during the stages of embryogenesis and early postnatal ontogenesis was investigated in this work.There were concluded populations of cells from the endocardium, myocardium, epicardium and pericardium, and so condensed and decondensed mesenchyma and conducted the additional analysis of the main histogenetic processes of embryonic rat heart in the context of the impact of the time factor using the results of the researches of lectins histotopography; it was set the nature of the acquisition of the definitive status of individual populations of cells and structures of the embryonic rat heart, the degree of proliferative and migratory processes in the heart of the fetus, as well as the presence and density of apoptotic regions.